Tanggung Jawab Bank sebagai Bentuk Perlindungan Hukum bagi Nasabah Penyimpan Simpanan Deposito - Alif Imaduddin Azzam; Inda Rahadian (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
Banks are obligated to ensure the security of funds deposited by the public in accordance with the Banking Law. In practice, issues concerning the loss of customers deposits frequently occur. Therefore, this research aims to examine the legal problems related to, first the liability of banks for the loss of customer deposit funds and second, the legal protection provided to customers in cases of lost deposit funds within a bank. This study employs a normative legal research method, utilizing statutory, conceptual, and case approach based on secondary data sources. The findings of this research conclude that banks bear responsibility for compensating the losses incurred from the disappearance of customer deposit funds, based on the principle of vicarious liability. The legal protection available to customers includes both preventive legal protections, as stipulated in Law on the Development and Strengthening of the Financial Sector, Financial Services Authority Regulation on Customer and Public Protection in Financial Services Sector, and the Financial Services Authority Regulation on Risk Management Implementation for Commercial Banks. As repressive legal protection is provided through complaint procedures and dispute resolution processes at the bank level, through the Financial Services Authority, and ultimately through the Financial Services Sector Alternative Dispute Resolution Institution or the courts.